Evaluasi dan Desain Ulang Jalur Pipa Suction Pompa Sentrifugal Berbasis Standar API RP 686 untuk Mitigasi Kavitasi - Abrar Ridwan; Ibnu Zaki; Sunaryo Sunaryo (LPPM Universitas Pahlawan Tuanku Tambusai, 2026)
This research aims to enhance operational reliability and prevent cavitation by evaluating and redesigning the pump's suction piping system in accordance with API RP 686 standard. The evaluation involved analyzing existing field data and comparing it against API RP 686, followed by suction pipeline redesign and Net Positive Suction Head Available (NPSHa) calculations for both conditions. The results show the existing NPSHa to be 4.78 meters, slightly below the pump's NPSHr (5 meters), indicating potential for cavitation due to existing piping configuration non-compliance with API RP 686. After redesign, NPSHa significantly increased to 7.27 meters, exceeding the pump's NPSHr, proving the new design effectiveness in eliminating cavitation.